2013
DOI: 10.5194/bgd-10-5499-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in soil carbon stocks in Brazil due to land use: paired site comparisons and a regional pasture soil survey

Abstract: In this paper we calculated soil carbon stocks in Brazil using 17 paired sites where soil stocks were determined in native vegetation, pastures and crop-livestock systems (CPS), and in other regional samplings encompassing more than 100 pasture soils, from 6.58° S to 31.53° S, involving three major Brazilian biomes: Cerrado, Atlantic Forest, and the Pampa. The average native vegetation soil carbon stocks at 10 and 30 cm soil depth were equal to approximately 33 and 65 Mg ha−1, respectively. In the p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
2
8
0
2
Order By: Relevance
“…Moreover, the conversion from forest to pasture increased C stocks within deeper soil layers (0-100 cm) in the Brazilian Amazon region near the BR163 road, in the Mato Grosso state [25]. A regional survey of pastures that included other Brazilian biomes, such as Cerrado, Atlantic Forest, and Pampas, [35] found that the absolute change in the SOC stocks during the conversion of native vegetation to pastures, indicated an average gain of C of 6.7 Mg·ha −1 compared to native vegetation, or relative gains of 15%. However, it is worth mentioning that those authors also reported losses of SOC following the conversion to pasture in 17 paired sites, highlighting the uncertainties (e.g., soil type and management) associated with soil sample data.…”
Section: Land Use and Management Changes Vs Soil C And N Stocksmentioning
confidence: 99%
“…Moreover, the conversion from forest to pasture increased C stocks within deeper soil layers (0-100 cm) in the Brazilian Amazon region near the BR163 road, in the Mato Grosso state [25]. A regional survey of pastures that included other Brazilian biomes, such as Cerrado, Atlantic Forest, and Pampas, [35] found that the absolute change in the SOC stocks during the conversion of native vegetation to pastures, indicated an average gain of C of 6.7 Mg·ha −1 compared to native vegetation, or relative gains of 15%. However, it is worth mentioning that those authors also reported losses of SOC following the conversion to pasture in 17 paired sites, highlighting the uncertainties (e.g., soil type and management) associated with soil sample data.…”
Section: Land Use and Management Changes Vs Soil C And N Stocksmentioning
confidence: 99%
“…Bulk density was obtained for each layer using the core method, by means of cylinders with volumetric rings 0.053 m high and 0.05 m in diameter. Detailed information can be found in Assad et al (2013).…”
Section: Data Setmentioning
confidence: 99%
“…We assumed that organic matter derived from C 3 plants has d 13 C value equal to -27.9% which is the lowest d 13 C measured in our five study areas, and plant organic matter derived from C 4 plants has a d 13 C 4 as -11.3% based on an broad isotopic analysis carried out in Brazil available elsewhere (see Assad et al 2013). The percentage contribution from C 4 -derived carbon is given by the following isotope dilution equation:…”
Section: Soil Analysismentioning
confidence: 99%